Mental Health Status and its Association with the Physical Health Status of Primary School Teachers in the Klang Valley, Malaysia - Abdul Samad, Nurul Izzah (2011)
Recent studies have shown that school’s physical and social environment can influence teachers’ health. This study determined the mental health status and its association with the physical health status among primary school teachers in the Klang Valley. Mental health status comprised the assessment of mental health and stress levels while the physical health status includes low back pain and respiratory symptoms. A cross sectional study was carried out in nine primary schools in the Klang Valley. The schools have been stratified according to urban, industrial and rural areas and randomly selected from a list obtained from the Malaysian Ministry of Education. Two hundred and seventy two respondents who fulfilled the study criteria volunteered to participate in the study. Self-administered questionnaires consisting of five sections, including demographic background, mental health assessment (General Health Questionnaire),work stress levels (Teacher Stress Inventory Questionnaire), low back pain (modified Nordic Musculoskeletal Questionnaire) and respiratory symptoms (American Thoracic Society Questionnaire) were distributed to the teachers. Study results showed that only 12.1% of the respondents had low mental health status and most of them experienced moderate work stress level (71.7%). Student misbehavior was the main stressor in the school environment. The prevalence of low back pain was 40.4% among the respondents. Lifting load (28.0%) was presumed by the respondents as the main factor that contributed to low back pain, followed by prolonged sitting (25.2%). Meanwhile, prevalence of cough (35.7%), phlegm (21.4%) and chest pain (8.3%) were highest in industrial school teachers; while wheezing (15.7%) and asthma (11.6%) were highest in urban school teachers. Mental health status has a direct significant association with work stress (p=0.018). Gender (p=0.001) and workload (p=0.002) were significant contributing factors to the mental health status. Poor mental health influenced the low back pain and respiratory symptoms significantly (OR 1.11, 95% CI 1.06-1.15; OR 1.09, 95% CI 1.04-1.15, respectively). These primary school teachers experienced medium level of stress. Gender and workload could influence the teachers to experience poor mental health. Teachers with poor mental health status had higher risk of developing low back pain and respiratory symptoms. Keywords: Mental Health Status, Work Stress, Low Back Pain, Respiratory Symptoms, Primary School Teachers